Evaluation of F6 RILs for Drought Tolerance in Green Gram [Vigna radiata (L.)] - Kanavi, M. S. P.; Somu, G.; Marappa, N.; Shashidhara, K. S.; Nagesh, N. (International Journal of Bio-resource and Stress Management, 2023)
An experiment was conducted at the experimental plot of College of Agriculture, Hassan, Karnataka, India during summer, i.e. January–April, 2018 with an objective to screen F6 RILs for drought tolerance using Augmented Randomized Block Design with 152 RILs, two parental lines and 5 check entries under drought stress condition. Thes F6 RILs are derived from cross between drought tolerant line VGG10-010 and drought susceptible AKL-225. Drought condition was imposed by withholding irrigation 25 days after sowing. The experiment was conducted in summer season, there were no unpredicted rains during the entire cropping period, hence the drought condition was effectively imposed. Analysis of variance (ANOVA) revealed highly significant mean squares attributable to F6 RILs for all the traits under investigation. Mean squares attributable to ‘RILs vs check entries’ were significant for all the traits except for harvest index and relative water content. The results suggest significant differences among the F6 RILs. The RILs as a group differed significantly for all of the traits under investigation, similarly, check entries as group differed significantly for all the traits except for harvest index which revealed high significant differences among 152 F6 RILs for yield, yield component traits and also for drought tolerance traits. Assessment of genetic variability in RILs will help in identifying best transgressive RILs and will ultimately decide the success of plant breeding programmes. Selection among straight RILs is effective only if trait is controlled by higher heritability, hence assessment of genetic variability assumes lot of importance.